Algas marinas bénticas de la costa del estado de Colima, México - Mateo-Cid, Luz Elena; Mendoza-González, A. Catalina (Instituto de Ecología, A.C., 1991)
Results are presented of a study on algae from the tropical waters of the coast of Colima, in the Mexican Pacific shore. The floristic list obtained ineludes data on distribution of species, reproductive stage, tidal level, mode, facies and epiphytism. Nine species of Cyanophyceae, 76 species and 1 variety of Rhodophyceae, 23 species of Phaeophyceae, 19 species of Bacillariophyceae and 26 species and 1 form of Chlorophyceae were identified. Species diversity was compared for two different climatic seasons, the rainy and the dry, during 1985, 1987 and 1988.Species diversity in relation to light, tides, facies and variation due to wet and dry climatic seasons is discussed. The Rhodophyceae are dominant in terms of diversity; in the other four classes minimal variation between species present in either of the two seasons was observed. The algal flora of Colima is tropical and its greatest diversity was found in the rainy season.